2006
DOI: 10.1172/jci29021
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis and biofilm-associated pili of Enterococcus faecalis

Abstract: Increasing multidrug resistance in Enterococcus faecalis, a nosocomial opportunist and common cause of bacterial endocarditis, emphasizes the need for alternative therapeutic approaches such as immunotherapy or immunoprophylaxis. In an earlier study, we demonstrated the presence of antibodies in E. faecalis endocarditis patient sera to recombinant forms of 9 E. faecalis cell wall-anchored proteins; of these, we have now characterized an in vivo-expressed locus of 3 genes and an associated sortase gene (encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

28
492
2
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 360 publications
(529 citation statements)
references
References 46 publications
28
492
2
7
Order By: Relevance
“…These included the gelatinase gene (22,26,28,30); recently described pilus-encoding genes (16); genes encoding putative MSCRAMMs (microbial surface components recognizing adhesive matrix molecules) with predicted immunoglobulin (Ig)-like folds (17,18,27; J. Sillanpää, S. R. Nallapareddy, and B. E. Murray, unpublished data); genes, including esp (33), in a predicted pathogenicity island (PAI) (15); and an acquired gene that contributes to biofilm formation (32) ( Table 1). The strain was examined for phenotypic production of gelatinase (22), hemolytic activity on Bacto Tryptic Soy Agar (Becton Dickinson and Company, Sparks, MD) plus 5% human blood agar plates, and biofilm formation (14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These included the gelatinase gene (22,26,28,30); recently described pilus-encoding genes (16); genes encoding putative MSCRAMMs (microbial surface components recognizing adhesive matrix molecules) with predicted immunoglobulin (Ig)-like folds (17,18,27; J. Sillanpää, S. R. Nallapareddy, and B. E. Murray, unpublished data); genes, including esp (33), in a predicted pathogenicity island (PAI) (15); and an acquired gene that contributes to biofilm formation (32) ( Table 1). The strain was examined for phenotypic production of gelatinase (22), hemolytic activity on Bacto Tryptic Soy Agar (Becton Dickinson and Company, Sparks, MD) plus 5% human blood agar plates, and biofilm formation (14).…”
mentioning
confidence: 99%
“…Subsequently, a family of seven genes encoding MSCRAMM-like proteins was found in 100% (nine out of nine) of the E. faecalis endocarditis strains tested, and elevated titers of IgG to these MSCRAMMlike proteins were found in the sera of nine patients with E. faecalis infections (27). Three of these genes, ebpA, ebpB, and ebpC (endocarditis-and biofilm-associated pili), control sur- face pilus formation and may be important in endocarditis pathogenesis (16). Biofilm formation, which is modulated by many genes, including esp and the fsr locus, likely serves as an important factor in E. faecalis infections (16,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The endocarditis-and biofilm-associated pili (Ebp) are surface-associated filamentous structures considered to play a pivotal role in Enterococcus faecalis virulence (Nallapareddy et al, 2006(Nallapareddy et al, , 2011bKemp et al, 2007;Singh et al, 2007;Nielsen et al, 2012;Sillanpää et al, 2013). Ebp pili are encoded by the ubiquitous ebpABC-bps cluster, which codes for the cell wall anchor pilin EbpB, the major shaft pilin EbpC and the fibre tip pilin EbpA.…”
Section: Introductionmentioning
confidence: 99%
“…Ebp pili are encoded by the ubiquitous ebpABC-bps cluster, which codes for the cell wall anchor pilin EbpB, the major shaft pilin EbpC and the fibre tip pilin EbpA. A pilusspecific class C sortase (Bps, for biofilm-and pilusassociated sortase), catalyses the assembly of the structural subunits into pili, before the housekeeping sortase A (SrtA) covalently binds the elongated pili to the cell wall via EbpB (Nallapareddy et al, 2006;Sillanpää et al, 2013). Studies on ebp regulation identified the upstream ebpR gene (Bourgogne et al, 2007) and the rnjB gene (Gao et al, 2010) as activators at the mRNA level, while the Fsr quorum-sensing system was described as a weak repressor (Bourgogne et al, 2006).…”
Section: Introductionmentioning
confidence: 99%